Competition for exclusivity and customer lock-in: Evidence from copyright enforcement in China - Youming Liu (Bank of Canada, 2023)
Copyright law grants copyright owners exclusive rights so that they have adequate financial incentives to create and innovate. However, when firms are copyright owners, they can leverage their right to sell or distribute products exclusively and thus obtain excessive financial gains. This paper studies the music streaming industry, where streaming services compete for exclusive licenses from music labels. Service providers use unique content to attract users, tailoring their services to individual preferences to create switching costs that lead to user lock-in. Using theoretical analysis and descriptive empirics, I show that exclusivity confers advantages in competition for a service that can generate larger lock-in effects. I then construct a dynamic structural model in which consumers face switching costs when making subscription decisions. I estimate the model using monthly data from China's music streaming market over 2014-17. Finally, I simulate market outcomes under two alternative policies: a compulsory licensing provision and a mandatory data portability policy. The policy simulation shows that compulsory licensing that enforces non-exclusive distribution would not improve market competition by "leveling the field" between dominant and small services as intended. On the contrary, this policy increases market concentration, enlarging the gap in market share between dominant and small services. In contrast, mandatory data portability that reduces switching costs would decrease market concentration, bringing more users to smaller services.
Keywords: L13; L42; L51; 330; Econometric and statistical methods; Firm dynamics; Market structure and pricing